Equity for the rare: a review on India’s rare disease challenges and policy responses - Aggarwal, Ashima; Sharma, Aaina; Dhiman, Shruti; Halder, Pritam (International Journal Of Community Medicine And Public Health, 2025)
Rare diseases, despite affecting a relatively small percentage of the population, impose significant health and economic burdens globally. India, with its vast genetic diversity and socio-cultural practices like consanguinity, faces unique challenges in managing rare diseases. The National Policy for Rare Diseases (NPRD) 2021 was introduced to streamline care, but major gaps persist in awareness, diagnosis, financing, and access. A scoping review was conducted using peer-reviewed literature, government reports, policy documents, and grey literature. Sources included Ministry of Health and Family Welfare, Indian Council of Medical Research, and advocacy organizations like Organization for Rare Diseases India. Data were analysed thematically across five domains: awareness, primary care, financial risk, health technology assessment, and policy responses. The review revealed significant deficits in rare diseases awareness among healthcare professionals and the public, with limited training and delayed diagnoses being common. Primary care lacks the resources for early genetic screening or effective referral systems. Financial burden remains high; treatments often exceed ₹1 crore, while financial aid caps at ₹50 lakhs. Health technology assessment methods are not adequately adapted for rare diseases, and orphan drug availability is hindered by regulatory and pricing barriers. While India has taken steps to improve rare disease care through the NPRD and policy reforms, critical barriers remain. Enhancing early diagnosis, revising health technology assessment frameworks for rare diseases, expanding local drug production, and integrating rare disease education into medical curricula are essential to achieving equitable and sustainable care for rare disease patients.